Outcome of bioprosthetic valve replacement in dogs with tricuspid valve dysplasia. (April 2017) - Bristow, P.; Sargent, J.; Luis Fuentes, V.; Brockman, D.
Abstract : Objectives: To describe the short‐term and long‐term outcome in dogs with tricuspid valve dysplasia undergoing tricuspid valve replacement under cardiopulmonary bypass. Methods: Data were collected from the hospital records of all dogs that had undergone tricuspid valve replacement under cardiopulmonary bypass between 2006 and 2012. Dogs were considered candidates for tricuspid valve replacement if they had severe tricuspid valve regurgitation associated with clinical signs of cardiac compromise. Results: Nine dogs of six different breeds were presented. Median age was 13 months (range 7 to 61 months), median weight 26·5 kg (range 9·7 to 59 kg). Eight bovine pericardial valves and one porcine aortic valve were used. One non‐fatal intraoperative complication occurred. Complications during hospitalisation occurred in six dogs, four of which were fatal. Of the five dogs discharged, one presented dead due to haemothorax after minor trauma seven days later. The four remaining dogs survived a median of 533 days; all of these dogs received a bovine pericardial valve. Clinical Significance: Based on our results, tricuspid valve replacement with bovine or porcine prosthetic valves is associated with a high incidence of complications.